Pengaruh Penggunaan Media Sosial terhadap Hasil Belajar Siswa Kelas IX SMP Negeri 2 Batang Peranap - Nanda Mulyani Pratiwi; A Julizar; Lilis Gusliyah; Miftahir Rizqa; Mhd Khairi Azhar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this study is to ascertain how social media use affects grade IX students' academic performance at SMP Negeri 2 Batang Peranap. Out of 90 pupils, 27 respondents participated in this quantitative study that took a correlational approach. A 4-point Likert scale (Strongly Agree to Strongly Disagree) was used in the questionnaire to examine the dependent variable (academic accomplishment) and the independent variable (social media use). A straightforward linear regression analysis revealed a strong inverse relationship between students' assessments of their academic performance and the amount of time they spend on social media. Therefore, students tend to perform worse academically the more they use social media. In order to increase productivity and facilitate learning activities, it is recommended that parents and teachers supervise and guide their children's use of social media.